Induced adsorption of pectin on copper-ion-modified galena surfaces: Flotation and adsorption mechanism. (1st November 2021) - Wang, Changtao; Liu, Runqing; Wu, Meirong; Zhai, Qilin; Sun, Wei; Jing, Nianwen; Xie, Feifei
Highlights: Pectin strongly inhibits copper-ion-modified galena flotation. Copper ions deposited on galena surface and improved surface reactivity. The adsorption thickness of pectin on galena surface increased after modification. The covered copper sulfides and hydroxides induced pectin chemically adsorption. Abstract: The development of organic depressants for sulfide mineral flotation has received widespread attention, and metal ions can enhance or weaken the depression effect of organic depressants. In this study, the flotation behavior of pectin-treated galena and chalcopyrite in the presence and absence of copper sulfate was investigated through micro-flotation tests. Results showed that pectin merely depressed galena and chalcopyrite flotation under alkaline conditions while selectively imparting strong hydrophilicity to the copper-sulfate-treated galena surface. Contact angle, reagent adsorption, zeta potential, and atomic force microscopy measurements were conducted to evaluate the effect of copper sulfate on pectin adsorption on galena surfaces. Overall, copper ions could deposit on galena surfaces, and the surface reactivity was improved due to the generation of highly conductive or positively charged copper substances. Furthermore, the adsorption thickness and capacity of pectin on modified galena surface was facilitated. X-ray photoelectron spectroscopy results further revealed that the covered copper sulfides and hydroxides induced pectin chemically adsorption to generate S–Cu–O and Cu–O–R species.